European National Libraries: A Review of the Year’s Activities - Smethurst, Michael (LIBER Quarterly: The Journal of the Association of European Research Libraries, 1999)
This review of the activities of the National Libraries in membership of the Conference of European National Libraries during last year has been compiled from the summary reports for 1998 submitted by the Directors to the CENL Secretariat at the Koniklijke Bibliotheek at The Hague in the Netherlands.